Strategi Dakwah Gerakan Jamaah Tabligh di Kota Pancor - Asror, M. Zainul (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2018)
In the past few years, the missionary movement of the Tablighi Jamaat has grown rapidly. In Pancor City this movement was fairly new, in less than 10 years, the Jama'at Tabligh could enter to spread its missionary mission and be well received by the community without disturbing the harmony of public relations. In fact, socially rooted Pancor was the center of the Nahdlatul Wathan Islamic mass organization. This study aims to determine the strategy of preaching the Jama'at Tabligh movement. The location of this study was in Pancor City, East Lombok Regency. The method used is descriptive qualitative research method. Data collection uses observation, interviews and documentation. The qualitative data analysis technique is to obtain a general and comprehensive picture of the preaching activities of the Jama'at Tabligh in Pancor City. The results of this study found that in carrying out the mission of the tabligh congregation preaching used the Attaqwa Pancor mosque as the center of the movement, because for pilgrims Tabligh the mosque became a sacred and blessed place as a center of Islamic activity since the time of the Prophet Muhammad.  Besides that, the location of the mosque is strategic so that it can reach all Pancorans. The da'wah strategy carried out by the Jama'at Tabligh di Pancor movement is the strategy of the traditional-cultural Islamic movement, in the following way: first invites to pray in congregation in the mosque, secondly builds (in-group feeling) towards new members, third revives the tradition of carrying out the Prophet's Sunnah SAW, and the fourth activates the PELMA (Students) movement.Keywords:  Strategy, Da’wah, Jama’at Tabligh